Dopaminergic Meso-Cortical Projections to M1: Role in Motor Learning and Motor Cortex Plasticity - Hosp, Jonas A.; Luft, Andreas R. (Frontiers in Neurology, 2013)
Although the architecture of a dopaminergic (DA) system within the primary motor cortex (M1) was well characterized anatomically, its functional significance remained obscure for a long time. Recent studies in rats revealed that the integrity of dopaminergic fibers in M1 is a prerequisite for successful acquisition of motor skills. This essential contribution of DA for motor learning is plausible as it modulates M1 circuitry at multiple levels thereby promoting plastic changes that are required for information storage: at the network level, DA increases cortical excitability and enhances the stability of motor maps. At the cellular level, DA induces the expression of learning related genes via the transcription factor c-fos. At the level of synapses, DA is required for the formation of long-term potentiation (LTP), a mechanism that likely is a fingerprint of a motor memory trace within M1. Dopaminergic fibers innervating M1 originate within the midbrain, precisely the ventral tegmental area (VTA) and the medial portion of substantia nigra (SN). Thus, they could be part of the meso-cortico-limibic pathway – a network that provides information about saliency and motivational value of an external stimulus and is commonly referred as